Analysis of Soil Moisture Characteristics and Deficit Compensation of Forest Land in Nanxiaohegou Watershed. Issue 3 (February 2020) - Zhang, Ling; Song, Xiaoyu; Fu, Na; Li, Lanjun; Zhang, Zhixu; Li, Huaiyou
Abstract: Exploring the soil water characteristics of typical afforestation species Robinia pseudoacacia and Platycladus orientalis in the gully region of the Loess Plateau, and analyzing the compensation situation of soil water storage deficit before and after the rainy season, it provides reference for the selection of planting tree species in the process of water and soil conservation. The analysis results show that, the soil moisture content of different vegetations is different, and the soil moisture in different slope directions also shows differences. Soil water storage has the same change rule. Soil moisture continued to increase in the range of 0-30cm. it keeps decreasing in the range of 30-60cm, it fluctuates within 10% below 60 cm depth. DSW of robinia pseudoacacia forest was lower than that of platycladus orientalis, and CSW was higher than that of platycladus orientalis. The DSW of the shady slope is lower than the sunny slope, and the CSW is higher than the sunny slope.